La herencia de la guerra: Salta (Argentina) 1821-1831 - Sara Emilia Mata (Nuevo mundo - Mundos Nuevos, 2012)
This article proposes a first approach to political participation of movilized men during independent war in Salta's jurisdiction, Argentina*. Our aim is to enter upon the compex political and social inheritance brought by the war. We will try to reconstruct some of it's main political and militar actors developements with a double pourpose: to take into account their political relationships with Bs. Aires and neibourgh states and also subaltern groups motives and political pourposes of those that played the rol of mediators between them and salteña elite members.